Folklore : an encyclopedia of beliefs, customs, tales, music, and art [Vol. one ( A-D)] - McCormick, Charlie T.; White, Kim Kennedy (England : ABC-CLID, 2011)
From the Publisher: Did you know that the tale of Cinderella is over 1,000 years old, and similar versions of this singular story exist in hundreds of cultures around the globe? Have you heard of "deathlore," a subgenre of folklore involving tombstones, coffins, cemeteries, and roadside memorial shrines? Did you realize that UFO sightings and cyber cultures constitute modern folklore? The broad field of folklore studies, developed over the past two centuries, provides significant insights into many aspects of human culture. While the term "folklore" conjures images of ancient practices and beliefs or folk heroes and traditional stories, it also applies to today's ever-changing cultural landscape. Even certain aspects of modern Internet-based popular culture and contemporary rites of passage represent folklore. This encyclopedia covers all the major genres of both ancient and contemporary folklore. This second edition adds more than 100 entries that examine the folklore practices of major ethnic groups, folk heroes, creatures of myth and legend, and emerging areas of interest in folklore studies.
Vol I. (A-D)
Includes index.
Keywords: Folklore -- Encyclopedias. Folklore